2020
DOI: 10.32615/ps.2020.056
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and nutrient-use efficiency in response to N and P addition in three dominant grassland species on the semiarid Loess Plateau

Abstract: Understanding the ecophysiological and nutrient-use strategies of dominant species is important for clarifying plant growth and an ecological process in their community under unbalanced N and P inputs. This study investigated effects of N and P addition [main plot: 0, 25, 50, and 100 kg(N) ha −1 year −1 ; subplot: 0, 20, 40, and 80 kg(P) ha -1 year -1 ] on leaf N and P contents (LNCa and LPCa), photosynthetic capacity (PNmax) and photosynthetic N-and P-use efficiencies (PNUE and PPUE) in three species (Stipa b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Soils in the semiarid Loess Plateau are commonly deficient in both nitrogen (N) and phosphorus (P) [ 15 ]. Previous studies in the region have shown that appropriate N and P fertilization could improve soil N and P availability and play a positive role in increasing grassland productivity and recovery of degraded grasslands [ 16 , 17 , 18 ]. On the other hand, the effects of the N and P addition on photosynthetic and leaf functional traits of dominant species, which are important for understanding underlying mechanisms of grassland community dynamics under N and P inputs, have only received limited attention in the regional grassland.…”
Section: Introductionmentioning
confidence: 99%
“…Soils in the semiarid Loess Plateau are commonly deficient in both nitrogen (N) and phosphorus (P) [ 15 ]. Previous studies in the region have shown that appropriate N and P fertilization could improve soil N and P availability and play a positive role in increasing grassland productivity and recovery of degraded grasslands [ 16 , 17 , 18 ]. On the other hand, the effects of the N and P addition on photosynthetic and leaf functional traits of dominant species, which are important for understanding underlying mechanisms of grassland community dynamics under N and P inputs, have only received limited attention in the regional grassland.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients addition could improve plant photosynthetic capacity by enlarging cell size and making the cell wall thinner to enhance stomatal conductance [ 56 ]. The variation of the net photosynthetic rate was inconsistent with that of stomatal conductance for some species, indicating that non-stomatal limitation (chlorophyll and carboxylation) may play an important role under N and P enrichment [ 28 , 57 , 58 ]. Overall, the different photosynthetic responses among the plant species in the alpine steppe suggested that long-term projected N and P addition may have the potential to change plant species composition and finally lead to the change of grassland community structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…In the alpine grasslands, responses to nutrient limitation may differ among species, this may be associated with the contrasting carbon and nutrient economies of different forms [ 25 , 26 ], and interspecific eco-physiological adaptations disparity [ 27 , 28 ]. There are also studies demonstrated that plants of different functional types show different photosynthetic capacity when the availability of N and P changes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations